2016
DOI: 10.21162/pakjas/16.5018
|View full text |Cite
|
Sign up to set email alerts
|

Cryopreservation of Shoot-Tips From Different Sugarcane Varieties Using D Cryo-Plate Technique

Abstract: Cryopreservation is an effective approach to conserve sugarcane germplasm for long term. This study was conducted to develop D cryo-plate technique to conserve sugarcane's shoot tips. This new and effective cryopreservation technique will serve the purpose to conserve sugarcane germplasm efficiently on the large scale at genebanks. Sugarcane variety Ni-1 were used to optimize the protocol and after optimization 11 other varieties were tested with optimized protocol. It was observed that shoot tips of Ni-1 with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…Similar to many orchid species such as Dendrobium Bobby Messina (Antony et al, 2010), Vanda Kaseem's Delight (Poobathy et al, 2012) and Brassidium Shooting Star (Mubbarakh et al, 2014), using larger (3-4 mm) SEs provided better viability compared to smaller SEs (1-2 mm) in postcryopreserved SEs via vitrification. With the V cryoplate method, large sugarcane shoot tips resulted in higher regrowth than smaller ones (Rafique et al, 2015). Melo et al (2011) also found that large explants could accumulate carbohydrate in the form of starch grains that could serve as an energy source for the regeneration of sugarcane shoot tips after cryopreservation.…”
Section: Resultsmentioning
confidence: 99%
“…Similar to many orchid species such as Dendrobium Bobby Messina (Antony et al, 2010), Vanda Kaseem's Delight (Poobathy et al, 2012) and Brassidium Shooting Star (Mubbarakh et al, 2014), using larger (3-4 mm) SEs provided better viability compared to smaller SEs (1-2 mm) in postcryopreserved SEs via vitrification. With the V cryoplate method, large sugarcane shoot tips resulted in higher regrowth than smaller ones (Rafique et al, 2015). Melo et al (2011) also found that large explants could accumulate carbohydrate in the form of starch grains that could serve as an energy source for the regeneration of sugarcane shoot tips after cryopreservation.…”
Section: Resultsmentioning
confidence: 99%
“…The application of V cryo-plate method has been reported for a wide range of species: strawberry [ 40 ], Dalmatian chrysanthemum [ 20 ], mint [ 42 ], mulberry [ 57 ], carnation [ 58 ], blueberry [ 59 ], mat rush [ 60 ], and sugarcane [ 61 ]. The satisfactory regrowth rates of cryopreserved potato shoot tips (96.7%) in V cryo-plate proved that it is a useful strategy for preserving valuable potato germplasm [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cryopreservation using aluminium V-cryoplates was developed for clonally propagated crops to ensure very high cooling and warming rates of treated explants [ 34 ]. The V-cryoplates procedure is known to produce high survival of cryopreserved plant tissues when compared with other methods [ 35 ]. In general, several studies reported that the preconditioning of shoot tips for 1 day in V-cryoplate experiments will produce very high recovery rates [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…The V-cryoplates procedure is known to produce high survival of cryopreserved plant tissues when compared with other methods [ 35 ]. In general, several studies reported that the preconditioning of shoot tips for 1 day in V-cryoplate experiments will produce very high recovery rates [ 34 , 35 ]. This is attributed mainly to the ability of in vitro tissues to adhere on the aluminium plates, resulting in a very rapid cooling after immersion in liquid nitrogen and very high warming rates in the unloading solution [ 20 , 36 ].…”
Section: Discussionmentioning
confidence: 99%